Synthesis of zirconium aminotrimethylene phosphonate nanorods and their application in toughened and flame retarded epoxy composites - Wang, Xin; Zhang, Jie; Fu, Xian-Ling; Chu, Fu-Kai; Hu, Yuan (Composites. Part A, Applied science and manufacturing, 2024)
•Novel zirconium aminotrimethylene phosphonate (ZrATMP) nanorods were synthesized.•The PHRR and THR of 3 wt% ZrATMP-EP were 30.4 % and 39.2 % lower than pure EP, respectively.•The TSR and peak CO production rate of 3 wt% ZrATMP-EP were 23.1 % and 47.3 % lower than pure EP, respectively.•The tensile and impact strengths of 3 wt% ZrATMP-EP increased by 110.7 % and 75.5 %, respectively, compared with pure EP. Nanocomposite technology is the most promising strategy to synchronously improve the mechanical properties and flame retardancy of polymer materials. In this study, zirconium aminotrimethylene phosphonate (ZrATMP) nanorods were synthesized from amino tris(methylene phosphonic acid) and added to epoxy resin (EP) to further prepare ZrATMP-EP composites. Compared with those of pure EP, the peak heat release rate, total heat release, total smoke release, and peak CO production rate of the 3 wt% ZrATMP-EP composite decreased by 30.4 %, 39.2 %, 23.1 %, and 47.3 %, respectively. This was because Lewis acid sites on the ZrATMP nanorods catalyzed the carbonization of the EP matrix to form a dense protective char layer. Additionally, the tensile and impact strengths of 3 wt% ZrATMP-EP were 110.7 % and 75.5 % greater than those of pure EP, respectively. ZrATMP nanorods are a new class of flame retardant additive because of the simultaneous improvements in fire safety and mechanical strength of polymers.